The role of human adenoviruses type 41 in acute diarrheal disease in Minas Gerais after rotavirus vaccination - Reis,Thaís Aparecida Vieira (2016)
Abstract Human adenovirus species F (HAdV-F) type 40 and 41 are commonly associated with acute diarrheal disease (ADD) across the world. Despite being the largest state in southeastern Brazil and having the second largest number of inhabitants, there is no information in the State of Minas Gerais regarding the role of HAdV-F in the etiology of ADD. This study was performed to determine the prevalence, to verify the epidemiological aspects of infection, and to characterize the strains of human adenoviruses (HAdV) detected. A total of 377 diarrheal fecal samples were obtained between January 2007 and August 2011 from inpatient and outpatient children of age ranging from 0 to 12 years. All samples were previously tested for rotavirus, norovirus, and astrovirus, and 314 of 377 were negative. The viral DNA was extracted, amplified using the polymerase chain reaction and the HAdV-positive samples were sequenced and phylogenetically analyzed. Statistical analyses were performed using the Chi-square test (p < 0.05), considering two conditions: the total of samples tested (377) and the total of negative samples for the remaining viruses tested (314). The overall prevalence of HAdV was 12.47% (47/377); and in 76.60% (36/47) of the positive samples, this virus was the only infectious agent detected. The phylogenetic analysis of partial sequences of 32 positive samples revealed that they all clustered with the HAdV-F type 41. The statistical analysis showed that there was no correlation between the onset of the HAdV infection and the origin of the samples (inpatients or outpatients) in the two conditions tested: the total of samples tested (p = 0.598) and the total of negative samples for the remaining viruses tested (p = 0.614). There was a significant association in the occurrence of infection in children aged 0–12 months for the condition 1 (p = 0.030) as well as condition 2 (p = 0.019). The occurrence of infections due to HAdV did not coincide with a pattern of seasonal distribution. These data indicate the significant involvement of HAdV-F type 41 in the etiology of ADD in Minas Gerais, which demonstrates the importance of other viral agents in the development of the disease after the introduction of rotavirus vaccine immunization.